1997
DOI: 10.1152/jappl.1997.83.6.2019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training and a single session of exercise on lipids and apolipoproteins in hypercholesterolemic men

Abstract: To differentiate between transient (acute) and training (chronic) effects of exercise at two different intensities on blood lipids and apolipoproteins (apo), 26 hypercholesterolemic men (cholesterol = 258 mg/dl, age = 47 yr, weight = 81.9 kg) trained three times per week for 24 wk, 350 kcal/session at high (80% maximal O2 uptake, n = 12) or moderate (50% maximal O2 uptake, n = 14) intensity. Serum lipid and apolipoprotein (apo) concentrations (plasma volume adjusted) were measured before and immediately, 24, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
2
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 40 publications
5
80
2
9
Order By: Relevance
“…If the "genes" for initial LDL-C or fitness levels 29 also affect the LDL response (ie, pleiotropic effect), then the adjustment would remove their effects and the heritability would decrease. These results are consistent with Crouse et al 32 who reported that changes in LDL-C vary depending on training level. Our results suggest this depen- Values are meanϮSD or percent.…”
Section: Rice Et Al Lipid Response To Trainingsupporting
confidence: 93%
See 1 more Smart Citation
“…If the "genes" for initial LDL-C or fitness levels 29 also affect the LDL response (ie, pleiotropic effect), then the adjustment would remove their effects and the heritability would decrease. These results are consistent with Crouse et al 32 who reported that changes in LDL-C vary depending on training level. Our results suggest this depen- Values are meanϮSD or percent.…”
Section: Rice Et Al Lipid Response To Trainingsupporting
confidence: 93%
“…For example, acute changes in LDL-C measured 24 hours after a bout of exercise were significant before training but not after 24 weeks of training. 32 In the HERITAGE study, the lipid and lipoprotein responses are considered to index chronic effects to exercise training in sedentary individuals. 15 Although previous results for chronic effects of training are inconsistent, increases in HDL-C and reductions in TC, LDL-C, and TG are often reported.…”
mentioning
confidence: 99%
“…Several of the studies have investigated the effects of combined exercise and diet on lipids and lipoproteins but few have looked at the effects of physical exercise alone (2,18). Physical exercise has long been acknowledged as an important part of a healthy lifestyle, and recent scientific evidence has linked regular physical exercise to a wide range of physical health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…[107][108][109][110][111][112][113][114][115][116][117][118] Exercise training increases the HDL-C level by 2.53 mg/dl, 110 which should be associated with a decrease in cardiovascular risk of approximately 7%, according to epidemiological data on the relationship between HDL-C and the risk of CAD. 11 However, physical activity is associated with a much greater reduction in the risk for developing CAD (30-35%).…”
Section: Hdl-c-raising and Atheroprotective Effects Of Exercisementioning
confidence: 99%